HUBUNGAN AYAT-AYAT KELESTARIAN LINGKUNGAN DALAM AL-QUR’AN, BIBEL, DAN TORAH DENGAN FILSAFAT LINGKUNGAN (ANALISIS INTERTEKTUALITAS JULIA KRISTEVA) - Shobibur Rizki Maulana (IAT IAIN Pontianak, 2022)
This paper discusses the preservation of nature from various religious scriptures and focuses on three holy books, namely the Qur'an, the Bibel, and the Torah. The universe is the responsibility of all human beings. However, in this modern era, a lot of human actions have emerged that can harm nature so the essence of its sustainability is not well maintained. Therefore, serious efforts are needed to preserve nature. This article uses a qualitative approach with a comparative analysis method. The result of this research is that from the point of view of environmental philosophy, the current economic crisis occurs because of the human paradigm itself. So religion, in this case, the texts of the scriptures, has an important position in restoring the holistic-ecological paradigm for the sake of creating the preservation of the natural environment.